Mechanical characterization of the lapping zone of palm wood trusses in the concrete - AKOWE, Sare; SOHOUNHLOUE, Jamik; MITCHOZOUNNON, Robert; FOUDJET, Erick Amos; GBAGUIDI AÏSSE, GÉRARD LÉOPOLD (My University, 2016)
The present article opens a new axis of the study of the palm as vegetable truss in the concrete and is based on the mechanical characterization of the lapping zone of palm wood trusses in the concrete. More explicitly, the finality of our study is to identify the type of bond that will give a maximal rigidity in the lapping zone. For that, it was question in a first time to count the different types of lapping existing in the literature, then to identify among the different types of lapping counted those which are better adapted to our study and finally to determine the type of lapping that offers the maximum of rigidity in bending four points. From the counted and retained lapping, we have achieved five types of beam to which we have added a witness beam. From the bending four points tests achieved, some results have been obtained and allow us to conclude that the type of bond that gives a maximal rigidity in the lapping zone is the bond of type 5; assembly by sticking of palm truss with galvanized tubes in U shape.
Keywords: palm wood; lapping zone; maximal rigidity; bending 4 points